Effect of molecular conformation on the mechanofluorochromic properties based on DDIF. (27th July 2017) - Mai, Runsheng; Peng, Huojun; Meng, Yuying; Chang, Xinyue; Jiang, Yue; Gao, Jinwei; Zhou, Guofu; Liu, Jun-ming
Abstract: Mechanofluorochromic (MFC) materials are smart materials in that their absorption and/or emission can respond to mechanical stimuli. They have received much attention recently. Although there have been several new material systems designed, little work has been done regarding the influence of molecular conformation on MFC properties. Herein, to disclose the relationship between molecular conformation and MFC properties, two molecules based on a 6, 12-Dihydro-6, 12-diaza-indeno[1, 2-b]fluorine (DDIF) building block with thienyl linker, BDDIF-Th andBDDIF-BTh, have been designed and synthesized. Optical and electrochemical properties have been studied by UV–vis spectrometer and cyclic voltammetry measurements. Weak aggregation-induced emission (AIE) phenomena were obtained in the tetrahydrofuran (THF)/water solution. MFC behaviors suggest thatBDDIF-Th is more sensible to the external mechanical forces thanBDDIF-BTh . The color change could be attributed to the appearance of new emission peak instead of a bathochromic or hypsochromic effect. Theoretical calculations reveal that MFC performance is highly related to the molecular conformation, meaning that theBDDIF-BTh with perpendicular conformation is more difficult to flatten than the comparatively planarBDDIF-Th .